Detection of ERBB2 (HER2) Gene Amplification Events in Cell-Free DNA and Response to Anti-HER2 Agents in a Large Asian Cancer Patient Cohort - Lee, Jeeyun; Franovic, Aleksandra; Shiotsu, Yukimasa; Kim, Seung Tae; Kim, Kyoung-Mee; Banks, Kimberly C.; Raymond, Victoria M.; Lanman, Richard B. (Frontiers in Oncology, 2019)
Background: HER2 antagonists have marked activity and are approved in the first-line for HER2 overexpressing breast and gastric (GC) cancers. Recent studies show that ERBB2 (HER2) gene amplification and overexpression may also be actionable in other tumor types. Inter- and intratumoral heterogeneity in HER2 status, however, poses a significant challenge in identifying patients that may benefit from HER2-targeted therapies. ERBB2 amplification as identified by circulating cell-free (cfDNA), which circumvents tissue heterogeneity issues, is emerging as a robust biomarker predictive of response to anti-HER2 agents. Here, the prevalence of ERBB2 alterations detectable by next-generation sequencing (NGS) of cfDNA was evaluated in a large cohort of Asian patients with advanced solid tumors. Methods: Results were queried for consecutive patients (n=469) tested by a comprehensive 73-gene cfDNA NGS assay (Guardant360) between November 2015 and June 2018. Patients with ERBB2 gene alterations including copy number amplifications (CNA), single nucleotide variants (SNV), and insertion-deletions (indel) were identified. Results: ERBB2 alterations were detected in 52 patients (11.1%); ERBB2 SNV, CNA, and indel were found in 27 (5.8%), 27 (5.8%), and 10 (2.1%) patients, respectively. ERBB2 amplification was most frequently identified in GC (21.4%; 6/28), CRC (11.1%; 5/45), lung (4%; 9/226), and breast (3.2%; 1/31) cancer patients. It was often mutually exclusive with other oncogenic drivers in GC (80%; 4/5) and CRC (50%; 2/4). High level ERBB2 copy number (CN) gains were observed in both GC and CRC (median CN 8.4 and 19.2, respectively). We further report two cases of advanced GC patients, one treatment naïve and the other having failed 4 lines of therapy, whose ERBB2 CNA was identified by cfDNA and derived clinical benefit from initiation of HER2-based therapies. Conclusion: Our data indicate that ERBB2 amplification is a common event in solid tumors among Asian cancer patients. Higher ERBB2 incidence and CN were observed in GC and CRC patients in the absence of other oncogenic alterations, underscoring its likely role as the driver alteration in those settings. Finally, we show the potential of comprehensive cfDNA testing in identifying patients who are most likely to benefit from HER2-targeted therapies.